2016
DOI: 10.1186/s12915-015-0224-3
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the human gut microbiota by dietary fibres occurs at the species level

Abstract: BackgroundDietary intake of specific non-digestible carbohydrates (including prebiotics) is increasingly seen as a highly effective approach for manipulating the composition and activities of the human gut microbiota to benefit health. Nevertheless, surprisingly little is known about the global response of the microbial community to particular carbohydrates. Recent in vivo dietary studies have demonstrated that the species composition of the human faecal microbiota is influenced by dietary intake. There is now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
225
4
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(251 citation statements)
references
References 53 publications
18
225
4
4
Order By: Relevance
“…In Figure 2, the microbial dynamics within the range of the studied dilution rates is presented on three taxonomic levels, phylum, family, and species, while differences can be seen mainly below the family level as also shown by Chung et al [9] The main phylum in both inocula, Firmicutes, remained dominant throughout the cultivation experiments. In De-stat cultures, the proportion of Bacteroidetes was higher at low dilution rates ( D  < 0.1 1/h) but not significantly in the NW culture on AP, while decrease was observed in the OW cultures on this substrate.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…In Figure 2, the microbial dynamics within the range of the studied dilution rates is presented on three taxonomic levels, phylum, family, and species, while differences can be seen mainly below the family level as also shown by Chung et al [9] The main phylum in both inocula, Firmicutes, remained dominant throughout the cultivation experiments. In De-stat cultures, the proportion of Bacteroidetes was higher at low dilution rates ( D  < 0.1 1/h) but not significantly in the NW culture on AP, while decrease was observed in the OW cultures on this substrate.…”
Section: Resultssupporting
confidence: 64%
“…Various in vitro models of the gut microbiota have been used to examine the effects of prebiotics [9,10], probiotics [11], and dietary modulations [12] on the gut microbiota and its metabolites. In vitro models facilitate frequent sampling and increased reproducibility [13].…”
Section: Introductionmentioning
confidence: 99%
“…This might be mediated by selected supplement addition for specific bacterial taxa that tolerate more acidic pH [33], since direct effect of probiotic supplements on the microbiota have not been demonstrated [14,34,35]. Also, acetic acid suppresses appetite [36] and propionate and butyrate acids modulate hormones such as GLP-1 and PYY, involved in satiety [5−7].…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that the response to a probiotic mix may be modulated by the initial microbiota configuration, the latter driving the permissivity to fermented food lactic acid bacteria [106,107]. Similarly, work by Chung et al indicates that depending on the presence/absence of specific fiber degraders, the microbiota may be totally irresponsive to specific fibers [108]. This will have to be documented further if we want to determine the degree of personalization made possible by nutritionbased strategies of modulation of the ecology of the human intestinal microbiota.…”
Section: Microbiota As Target For Functional Modulation Functional Numentioning
confidence: 99%